Al-Hadm dalam Talak Bain Sughra Menurut Imam Malik - Altafiah, Ahmad; Andrayuni, Lilik (LPPM STIS Hidayatullah, 2023)
Imam Malik and Abu Hanifah have different opinions regarding divorce (talak). According to Imam Malik, talak one and talak two are not nullified if a woman marries another man and then returns to her first husband. Only talak three can nullify the previous divorces. Abu Hanifah believes that such a marriage can nullify talak three as well as the preceding divorces before talak three is pronounced. This research is a literature study using a normative approach to determine the legal basis for nullifying the number of divorces in specific situations. The deductive-inductive method is employed to draw conclusions from the research findings. Imam Malik utilizes various sources, including the Qur'an, Sunnah, ijma' Ahl Madinah, fatwas of the Companions, khabar ahad, qiyas, istishan, Al-maslahah Al-mursalah, and sad al-Zara'i, to establish the legal rulings. He refers to the fatwas of the Companions, particularly the jurisprudence of Umar Ibn Khattab, to explain al-hadm (continuation of the remaining divorces) in talak sughra. The purpose is to encourage husbands and wives to exercise caution and not misuse divorce, providing an opportunity for husbands to mend the broken bonds of marriage. However, Imam Malik's opinion is less relevant to the development of Islamic law in Indonesia. In Indonesian marriage fiqh, talak three nullifies the preceding divorces, aligning with the opinion of Abu Hanifah based on the Qur'anic foundations.